Aspen SUCROSE TRANSPORTER3 Allocates Carbon into Wood Fibers(1)([C])([W]) - Mahboubi, Amir (American Society of Plant Biologists, 2013)
Wood formation in trees requires carbon import from the photosynthetic tissues. In several tree species, including Populus species, the majority of this carbon is derived from sucrose (Suc) transported in the phloem. The mechanism of radial Suc transport from phloem to developing wood is not well understood. We investigated the role of active Suc transport during secondary cell wall formation in hybrid aspen (Populus tremula × Populus tremuloides). We show that RNA interference-mediated reduction of PttSUT3 (for Suc/H(+) symporter) during secondary cell wall formation in developing wood caused thinner wood fiber walls accompanied by a reduction in cellulose and an increase in lignin. Suc content in the phloem and developing wood was not significantly changed. However, after (13)CO(2) assimilation, the SUT3RNAi lines contained more (13)C than the wild type in the Suc-containing extract of developing wood. Hence, Suc was transported into developing wood, but the Suc-derived carbon was not efficiently incorporated to wood fiber walls. A yellow fluorescent protein:PttSUT3 fusion localized to plasma membrane, suggesting that reduced Suc import into developing wood fibers was the cause of the observed cell wall phenotype. The results show the importance of active Suc transport for wood formation in a symplasmically phloem-loading tree species and identify PttSUT3 as a principal transporter for carbon delivery into secondary cell wall-forming wood fibers.